Women’s Participation in Livestock Management without using Advance Means of News and Information: A case study of Rural Women in Pakistan - Noreen, Sidra; Nazmine; Tareen, Hannan Khan; Tareen, Dr. Manan Khan; Ahmad, Shabbir (The journal of contemporary issues in business and government, 2021)
Pakistan is an agricultural country and the main focus of the agriculture economy. Women's participation in livestock production and development has been a long-standing global tradition. Keeping in mind the role and participation of women in livestock management in rural areas of the Punjab, the current study is aimed to investigate the socio-economic conditions of those women who are participating in livestock management. The role of women in managing livestock and the effect of education, age, family system, and family income on women participation in livestock is also the focus of the current study. Cross sectional research design is selected for descriptive and explanatory research objectives because there is no time dimension involved. The researcher selected four Tehsils of Punjab. Data is collected using questionnaire as tool of data collection and both descriptive and inferential statistics is applied to present, summarize and test hypothesis of the study. They are found taking part in major task related to manage livestock such as collecting foder, chopping foder, cleaning animals huts, watering, milking and finalizing the dairy products and they are also involved in selling these products in market as well. Because of illiteracy, they are not found using advance means of news and information. Age, education and family income of the respondents had significant association with managing and taking part in livestock management.